Integrated GWAS and transcriptomic analysis reveal the candidate salt-responding genes regulating Na+/K+ balance in barley (Hordeum vulgare L.) - Xu, Tingting; Meng, Shan; Zhu, Xiaopin; Di, Jiachun; Zhu, Yin; Yang, Xin; Yan, Wei (Frontiers in Plant Science, 2023)
Salt stress is one of the main abiotic stresses affecting crop yield and quality. Barley has strong salt tolerance, however, the underlying genetic basis is not fully clear, especially in the seedling stage. This study examined the ionic changes in micro-core barley germplasms under the control and salt conditions. Genome-wide association study (GWAS) analysis revealed 54 significant SNPs from a pool of 25,342 SNPs distributed in 7 chromosomes (Chr) of the Illumina Barley 50K SNP array. These SNPs are associated with ion homeostasis traits, sodium (Na+) and potassium (K+) content, and Na+ / K+ ratio representing five genomic regions on Chr 2, 4, 5, 6, and 7 in the leaves of worldwide barley accessions. And there are 3 SNP peaks located on the Chr 4, 6, and 7 and are associated with two and more traits, suggesting that these could be the hot spots regions of salt-tolerance candidate genes. Furthermore, 616 unique candidate genes were screened surrounding the significant SNPs, which are associated with transport proteins, protein kinases, binding proteins, and other proteins of unknown function. Meanwhile, transcriptomic analysis (RNA-Seq) was performed to screen out the related candidate genes in barley. Combined GWAS and RNA-Seq analysis revealed 8 promising salt-responding genes (PGK2, BASS3, SINAT2, AQP, SYT3, receptor kinase 2, GsSRK, and MATE) from the hot spot regions, which were verified between the salt-tolerant and salt-sensitive varieties by qRT-PCR. In all, these results provide candidate SNPs and genes responsible for salt tolerance in barley, and a new idea for studying such genetic basis in similar crops.